Comparison of effects of alcaftadine and olopatadine on conjunctival epithelium and eosinophil recruitment in a murine model of allergic conjunctivitis - Santa J Ono; Keith Lane (Dove Medical Press, 2011)
Santa J Ono1, Keith Lane21Emory University School of Medicine and Emory Eye Center, Dobbs Ocular Immunology Laboratories, Atlanta, GA, USA; 2Ora Inc., 300 Brickstone Square, Andover, MA, USABackground: Antihistamines constitute the first line of therapy for allergic conjunctivitis, and are safe and effective in relieving the signs and symptoms of ocular allergy. Despite this, they are less effective than some other drugs in relieving delayed symptoms of allergic conjunctivitis. Recent evidence suggests that changes in the conjunctival epithelium may underlie aspects of delayed reactions. In this study we compared two antihistamines, olopatadine and alcaftadine, for their ability to modify epithelial cell changes associated with allergic conjunctivitis at time points selected to reflect late-phase reactions.Methods: Studies employed a modified conjunctival allergen challenge model. Sensitized mice were challenged with topical allergen with or without drug treatments. Treatment groups were assayed for acute-phase (15 minutes) and delayed-phase (24 hours) responses. Groups were scored for allergy symptoms (redness, itch, tearing, and edema) and for conjunctival mast cell numbers. Delayed-phase groups were also examined for eosinophil numbers and for tight junctional protein expression.Results: Olopatadine-treated and alcaftadine-treated animals had similar efficacy profiles and mast cell numbers, suggesting both were effective at ameliorating symptoms of the acute phase. In contrast, alcaftadine-treated animals had significantly lower conjunctival eosinophil infiltration than either controls or olopatadine-treated animals. Allergen challenge caused a significant decrease in expression of the junctional protein, ZO-1, and this decrease was prevented by alcaftadine but not by olopatadine.Conclusion: Alcaftadine displays therapeutic properties beyond its antihistamine action. These include an ability to reduce conjunctival eosinophil recruitment, and a protective effect on epithelial tight junction protein expression.Keywords: alcaftadine, olopatadine, ocular allergy